PENGUATAN NILAI PANCASILA SEBAGAI UPAYA PENCEGAHAN TERHADAP PAHAM TERORISME PADA SISWA SMA NEGERI 4 PEKANBARU - Nurul Jannah Ramadhan; Putri Thamara Utami; Laila Nursalam; Ilham Hudi (CV. Denasya Smart Publisher, 2026)
Radicalism and terrorism pose a serious threat to national unity, particularly for young people who are in the process of searching for their identity, making senior high schools a strategic environment for prevention efforts through the strengthening of Pancasila values; the Community Service activity at SMA Negeri 4 Pekanbaru on November 27, 2025, involving 45 students and facilitated by 8 lecturers from Universitas Muhammadiyah Riau, was carried out through a socialization program in the form of a presentation themed “Pancasila: Learning to Prevent Terrorism Together”, delivered in a communicative and contextual manner, which generated positive responses from students who enthusiastically participated in the activity, and is expected to foster awareness of the importance of Pancasila values as an ideological safeguard against radicalism and terrorism from an early age.